1 / 7

# EXAMPLE 3

56 x 7 y 4. 7 x 4 y 3. 8 x 3 y. 8 xy 3. =. 4 y. 2 x y 2. 8 7 x x 6 y 3 y. =. 7 x 6 y. =. 8 x y 3. ANSWER. The correct answer is B. EXAMPLE 3. Standardized Test Practice. SOLUTION. Multiply numerators and denominators. Factor and divide out common factors.

## EXAMPLE 3

An Image/Link below is provided (as is) to download presentation Content is provided to you AS IS for your information and personal use only. Download presentation by click this link. During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

### Presentation Transcript

1. 56x7y4 7x4y3 8x 3y 8xy3 = 4y 2x y2 8 7 x x6y3y = 7x6y = 8 x y3 ANSWER The correct answer is B. EXAMPLE 3 Standardized Test Practice SOLUTION Multiply numerators and denominators. Factor and divide out common factors. Simplified form

2. 3x –3x2 x2 + x – 20 x2 + x – 20 x2 + 4x – 5 3x 3x 3x –3x2 3x(1– x) x2 + 4x – 5 (x –1)(x +5) (x + 5)(x – 4) = 3x 3x(1– x)(x + 5)(x – 4) = (x –1)(x + 5)(3x) 3x(–1)(x – 1)(x + 5)(x – 4) = (x – 1)(x + 5)(3x) 3x(–1)(x – 1)(x + 5)(x – 4) = (x – 1)(x + 5)(3x) EXAMPLE 4 Multiply rational expressions Multiply: SOLUTION Factor numerators and denominators. Multiply numerators and denominators. Rewrite 1– xas (– 1)(x – 1). Divide out common factors.

3. ANSWER –x + 4 EXAMPLE 4 Multiply rational expressions = (–1)(x – 4) Simplify. = –x + 4 Multiply.

4. x + 2 x + 2 x + 2 Multiply: (x2 + 3x + 9) (x2 + 3x + 9) x3 – 27 x3 – 27 x3 – 27 x2 + 3x + 9 = 1 (x + 2)(x2 + 3x + 9) (x + 2)(x2 + 3x + 9) = = (x – 3)(x2 + 3x + 9) (x – 3)(x2 + 3x + 9) x + 2 x + 2 = x – 3 x – 3 ANSWER EXAMPLE 5 Multiply a rational expression by a polynomial SOLUTION Write polynomial as a rational expression. Factor denominator. Divide out common factors. Simplified form

5. 6xy2 3x5 y2 8. 8xy 9x3y 18x6y4 6xy2 3x5 y2 = 72x4y2 2xy 9x3y 18 x4y2x2y2 = 18 4 x4 y2 x2y2 = 4 for Examples 3, 4 and 5 GUIDED PRACTICE Multiply the expressions. Simplify the result. SOLUTION Multiply numerators and denominators. Factor and divide out common factors. Simplified form

6. 2x(x –5) (x –5)(x +5) 2x2 – 10x x + 3 x2– 25 2x2 x + 3 = (x) 2x 2x(x –5) (x + 3) = (x –5)(x + 5)2x (x) 2x(x –5) (x + 3) = (x –5)(x + 5)2x (x) x + 3 = x(x + 5) for Examples 3, 4 and 5 GUIDED PRACTICE 2x2 – 10x x + 3 9. x2– 25 2x2 SOLUTION Factor numerators and denominators. Multiply numerators and denominators. Divide out common factors. Simplified form

7. x + 5 x2+x + 1 x3– 1 x + 5 x2+x + 1 = (x – 1) (x2+x + 1) 1 (x + 5) (x2+x + 1) = (x – 1) (x2+x + 1) (x + 5) (x2+x + 1) = (x – 1) (x2+x + 1) x + 5 = x – 1 for Examples 3, 4 and 5 GUIDED PRACTICE x + 5 10. x2+x + 1 x3– 1 SOLUTION Factor denominators. Multiply numerators and denominators. Divide out common factors. Simplified form

More Related